Retroviral vector-mediated high-efficiency expression of adenosine deaminase (ADA) in hematopoietic long-term cultures of ADA-deficient marrow cells. - Bordignon, C (1989)
Two recombinant retroviral vectors encoding the cDNA of the human adenosine deaminase (ADA; EC 3.5.4.4) gene and the bacterial neomycin resistance (Neo) gene have been used to transduce bone marrow cells obtained from four patients affected by the ADA-deficient variant of severe combined immunodeficiency. By utilizing the long-term marrow culture system, freshly isolated bone marrow cells were subjected to multiple infection cycles with cell-free supernatants containing high titers of viral vector and then maintained in long-term marrow culture in the absence of any overt selection pressure. By using this experimental protocol, about 30-40% of the hematopoietic progenitors were productively transduced with the viral vector, as judged by the appearance of G418-resistant colonies derived from granulocyte/macrophage and multipotent hematopoietic progenitor cells. The vector-encoded human ADA gene was expressed efficiently in both the myeloid and lymphoid progeny of the cultured bone marrow cells, reaching levels between 15% and 100% as compared to the levels of ADA in normal bone marrow cells. The efficiency of gene transfer and ADA production was proportional to the number of infection cycles. Furthermore, transduction of the ADA vectors into the bone marrow cells derived from an ADA-deficient patient restored the capacity of the cells to respond to phytohemagglutinin and interleukin 2.